Partisipasi Masyarakat dalam Pengembangan Desa Wisata Gurun Telaga Biru - Darmanto Darmanto; Meita Istianda; Faizal Madya (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2023)
This study aims to study how community participation in the development of the Telaga Biru Desert Tourism Village program. This study uses a qualitative method. The results of the study show that participation in the development of the Telaga Biru Desert Tourism Village is not comprehensive for all levels of society because the development of the Tourism Village is managed by a group of people who work together or are coordinated by BUMDes of Busung Village, Bintan Regency. The form of working relationship among group members is not top-down in nature but provides an opportunity for group members to participate in the form of ideas or suggestions for the development of the tourism village. The conclusion of this research is that it is hoped that BUMDes will be more intense in encouraging participation, especially group members in the development of the Telaga Biru Desert Tourism Village so that the income of community members can be further increased because the impact of the Covid-19 outbreak has caused the development activities of the Telaga Biru Desert Tourism Village to be less than optimal. Keywords : Participation, Tourism Village, Tourism Village Development